Нормальна складова швидкостi горiння газового факела - Trofimenko, M. Yu.; Aslanov, S. K.; Dragan, G. S.; Smolyar, V. P. (Publishing house "Academperiodika", 2018)
We study the burning of an open flame of hydrocarbon fuel in the air atmosphere and introduce a method of determination of the flame speed normal component for a selected local diametrical slice. A distribution of speeds along the flame axis reveals the inner flame structure and its variation depending on the fuel-oxidant ratio.